2019
DOI: 10.1111/jopr.13100
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Impression Material with Antimicrobial Properties for Dental Application

Abstract: Purpose To evaluate the antimicrobial activity and physico‐mechanical properties of an irreversible hydrocolloid in which nanostructured silver vanadate decorated with silver nanoparticles (AgVO3) was added at various concentrations (0% ‐ control, 2.5%, 5%, and 10% by weight). Materials and Methods The agar diffusion method (n = 10) was used to evaluate the inhibitory effect on the following species: Streptococcus mutans, Staphyloccocus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Several studies have evaluated the effect of the incorporation of nanostructured silver vanadate decorated with silver particles to endodontic cement [ 14 , 18 , 19 , 20 , 21 ]. Teixeira et al., 2019 [ 20 ] found that after modifying sealer, Endomethasone N and AH-Plus endodontic cement with the addition of 2.5, 5 and 10% β-AgVO 3 , there was better inhibition for the groups of 5 and 10% for Sealer, 2.5, 5 and 10% for Endomethasone, while AH-Plus presented similar results to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have evaluated the effect of the incorporation of nanostructured silver vanadate decorated with silver particles to endodontic cement [ 14 , 18 , 19 , 20 , 21 ]. Teixeira et al., 2019 [ 20 ] found that after modifying sealer, Endomethasone N and AH-Plus endodontic cement with the addition of 2.5, 5 and 10% β-AgVO 3 , there was better inhibition for the groups of 5 and 10% for Sealer, 2.5, 5 and 10% for Endomethasone, while AH-Plus presented similar results to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…De Castro et al., 2019 [ 21 ] evaluated the effect of the incorporation of β-AgVO 3 in 2.5, 5 and 10% in an irreversible hydrocolloid and obtained results that the addition demonstrated antimicrobial effects and dependent dose, except for P. aeruginosa and Streptococcus aureus. Regarding the time of gelatinization of the material, there were no significant differences in relation to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In dentistry, the β-AgVO 3 was incorporated in several dental materials such as acrylic resins, denture liners, impression materials, endodontic sealers, and prosthetic components, and demonstrated antimicrobial activity against Streptococcus mutans, Candida albicans, Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis and Escherichia coli [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%